Pengembangan Sistem Informasi Manajemen Reward Pelanggan Berbasis Website pada Pepito Market Cabang Sanur - Ni Made Rai Arini Permatasari; Retno Indah Rokhmawati; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Pepito Market Sanur Branch is one of the branches of Pepito Group. Pepito Group was established 2001 in Tuban, Jimbaran-Badung, Bali and already has more 20 branches in Bali. Pepito market implements Customer Relationship Management strategy to bind customers giving rewards to customers who have been shopping at Pepito Market by giving points. There are some things that become obstacles for customers and marketing of Pepito. Customers must come directly to the store and meet customer service to check their points. Marketing Pepito prints promotional catalogs in the form of flayers and distributes around the store to provide promotional information every month. This research will develop Information Management System of Customer Based Reward Based on Sanur Market Branch of Pepito Market. Implement operational CRM domain marketing automation and use webservice to combine Reward Management Information System with Pepito Cashier System. The system has several features: checking number of points, exchanging points, viewing catalogs, cataloging, editing catalogs and deleting catalogs. This system was developed using SDLC method using waterfall model. Final stages the system tested using black box method with 88% valid test result, white box with 100% valid test result and utility system for customer with 83% valid test result.